Output current observation and control of grid-connected modular multilevel converter using a simplified super twisting algorithm sliding mode - Imane Alia; Imad Merzouk; Mehamed Mounir Rezaoui; Hegazy Rezk; Abderezak Lashab (Results in Engineering)
This paper presents a method for observing and controlling the output current of a grid-connected Modular Multilevel Converter (MMC) using a Simplified Super Twisting Algorithm-Sliding Mode (SSTA-SM). This strategy effectively observes and controls the output current under steady-state and dynamic conditions. For the current observation, a Simplified Super Twisting Algorithm-Sliding Mode Luenberger Observer (SSTA-SMLO) is employed. This observer combines the simplicity of the Luenberger Observer (LO) with the robustness of the SSTA-SMO, providing high estimation accuracy while reducing system complexity. Moreover, the proposed Simplified Super Twisting Algorithm-Sliding Mode Control (SSTA-SMC) strategy ensures excellent control performance while maintaining the important features of traditional Sliding Mode Control (SMC). A MATLAB-based simulation and comparative analysis were conducted, evaluating SSTA-SMLO and SSTA-SMC against a Sliding Mode Observer (SMO) and a conventional proportional-integral (PI) controller. The results demonstrate that SSTA-SMC and SSTA-SMLO surpass the classic methods.